2022
DOI: 10.3390/cells11233889
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol Modulates Cerebellar Circuit Activity and Reduces Tremor

Abstract: Tremor is the most common movement disorder. Several drugs reduce tremor severity, but no cures are available. Propranolol, a β-adrenergic receptor blocker, is the leading treatment for tremor. However, the in vivo circuit mechanisms by which propranolol decreases tremor remain unclear. Here, we test whether propranolol modulates activity in the cerebellum, a key node in the tremor network. We investigated the effects of propranolol in healthy control mice and Car8wdl/wdl mice, which exhibit pathophysiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 143 publications
0
14
0
Order By: Relevance
“…To test this, we used Car8 wdl/wdl mice. We previously showed that Car8 wdl/wdl mice exhibit a severe oscillatory tremor that can be reduced to control levels by treatment with the beta blocker drug propranolol (36), which is used to treat tremor in human patients. Car8 wdl/wdl mice also exhibit ataxia and dystonia, which are not normalized by propranolol (10,22,26,36).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To test this, we used Car8 wdl/wdl mice. We previously showed that Car8 wdl/wdl mice exhibit a severe oscillatory tremor that can be reduced to control levels by treatment with the beta blocker drug propranolol (36), which is used to treat tremor in human patients. Car8 wdl/wdl mice also exhibit ataxia and dystonia, which are not normalized by propranolol (10,22,26,36).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that Car8 wdl/wdl mice exhibit a severe oscillatory tremor that can be reduced to control levels by treatment with the beta blocker drug propranolol (36), which is used to treat tremor in human patients. Car8 wdl/wdl mice also exhibit ataxia and dystonia, which are not normalized by propranolol (10,22,26,36). We found that, before treatment, Car8 wdl/wdl mice exhibited a large proportion of neurons with the tremor signature (8/13).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations